Cultures of identification in Napoleonic Italy, c.1800-1814 - Poggi, Stefano (Historian) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Through the lens of identification procedures, this book examines how the processes of state-building affected European societies during the Napoleonic period. By focusing on the Kingdom of Italy, the author shows how the top-down change usually associated with Napoleonic state-building had to compete and share spaces with the agencies of other often-neglected actors such as local bureaucrats, the clergy, and common people. What emerges is the coexistence of different understandings of personal identities, defined as "cultures of identification". One was rooted in the traditional habits of the population and based on a continuous performance of identities, allowing for a certain degree of fluidity. The other, promoted by the Napoleonic administration, envisaged legal and fixed identities that were to be managed directly by agents of the state. Personal identification in Napoleonic Italy was thus more of a battleground than a mere field of action for the "modernizing" activities of state authorities. Analyzing a period of momentous change for European societies, Cultures of Identification can be profitably read by students and researchers interested in the history of state-building, policing, social control, and personal identification"--
Imagining identities : the making of a culture of identification -- Policing identities : identity documents in an urban context -- Identity intermediaries : civil registration in the department of the Adriatico -- Ambiguous partners : the clergy -- A situational use : the population and the new identification system -- An active indifference : the people and civil registration.
Keywords: Registers of births, etc. -- Italy (Kingdom, 1805-1814) -- History; Identification -- Italy (Kingdom, 1805-1814) -- History; Public administration -- Italy (Kingdom, 1805-1814) -- History; Italy (Kingdom, 1805-1814) -- Politics and government; Italy -- Politics and government -- 1789-1815.; HISTORY / General; HISTORY / Europe / France; HISTORY / Europe / Italy